The five senses: hearing - Parramon, Jose Maria (New York : Barron's Educational Series, Inc, 1985)
A short scientific explanation of our sense of hearing, with a diagram of the ear.
Translation of: Los cinco sentidos- el oido
Keywords: Hearing-Juvenile literature; Hearing; Ear; Senses and sensation